UNSUR-UNSUR KRIMINALITAS DALAM NOVEL TANAH PARA BANDIT KARYA TERE LIYE: TINJAUAN SOSIOLOGI SASTRA DAN IMPLIKASINYA TERHADAP PEMBELAJARAN BAHASA INDONESIA - Dilla Arianti; Dewi Ferawati; Effiyadi (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2026)
The objectives of this study are: 1) To describe and analyse the forms of criminality in the novel Tanah Para Bandit by Tere Liye. 2) To describe and analyse the factors underlying the occurrence of criminality in the novel Tanah Para Bandit by Tere Liye. 3) To describe and analyse the implications of studying criminality for Indonesian language learning in senior secondary schools. This study employs a qualitative approach using a literature review methodology. Data collection techniques include literature review and documentation. The data analysis techniques used are data collection, data reduction, data presentation, and conclusion. The data validity techniques employed are observational rigour and referential adequacy. The research findings conclude that: 1) The forms of criminality present in the novel Tanah Para Bandit by Tere Liye include: economic crime, violent crime, and political crime. 2) The factors underlying the occurrence of criminality in the novel Tanah Para Bandit are poverty and low levels of education. 3) The implications for Indonesian language learning in senior secondary schools from the novel *Tanah Para Bandit* include critical reading skills, understanding of social and cultural context, vocabulary enrichment and language comprehension, class discussions and activities, and the value of supplementary books (non-fiction) and drama books (fiction).